Between Dependency and Autonomy - Grieco, Joseph M. (Berkeley, CA : University of California Press, 2020)
This title is part of UC Press's Voices Revived program, which commemorates University of California Press's mission to seek out and cultivate the brightest minds and give them voice, reach, and impact. Drawing on a backlist dating to 1893, Voices Revived makes high-quality, peer-reviewed scholarship accessible once again using print-on-demand technology. This title was originally published in 1984.
Frontmatter -- Contents -- Tables -- Acknowledgments -- Abbreviations -- Chapter I. Introduction -- Chapter II. India's Changing Fortunes in Computing, 1960-1980 -- Chapter III. The International Creation of Computer Opportunities -- Chapter IV. India's Exploitation of International Opportunities -- Chapter V. Policies, Politics, and Computers in India -- Chapter VI. Conclusion -- Notes -- Bibliography -- Index
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 23. Apr 2021).
JSTOR
Keywords: Computer industry -- India; International business enterprises -- India; Informatique -- Industrie -- Inde; Entreprises multinationales -- Inde; NON-CLASSIFIABLE.; Computer industry; International business enterprises; India